Waterproof locking agent for oil field fracturing and production process thereof

By preparing a composite surfactant with hydrophilic and hydrophobic groups, the problem of high surface tension of existing waterproof locking agents is solved, the waterproof locking effect is significantly improved, and the water locking damage during oil field fracturing is reduced.

CN119799308AActive Publication Date: 2025-04-11KELAMAYI XINJU IND & TRADE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510291236.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The existing waterproof locking agent has high surface tension and the waterproof locking effect is not ideal, making it difficult to meet the needs of water lock damage during oil field fracturing.

Method used

The intermediate is prepared by reacting N-hydroxysulfonate succinimide and ethylene oxide as reactants, and then reacting with 3,5-bis(trifluoromethyl)phenyl isocyanate to form a composite surfactant with hydrophilic and hydrophobic groups.

Benefits of technology

It reduces the water absorption on the rock surface, reduces the damage of water locks, and improves the practical application value of waterproof locking agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799308A_ABST
    Figure CN119799308A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oilfield exploitation, and discloses a water blocking preventing agent for oilfield fracturing and a production process thereof.The water blocking preventing agent is formed by mixing a composite surface active agent and purified water, wherein the hydrophilic group is a sulfonic acid group, succinimide and polyether, the hydrophobic group is phenyl fluorine, so that the surfactant belongs to an anionic and nonionic composite surfactant, and the polyether has a straight-chain structure, so that the polyether can gradually extend into a stone seam and further enter the deep part of a capillary tube, and the capillary tube is more uniform. Then ether bonds in the polyether structure and rock form hydrogen bonds, then the hydrogen bonds are attached to the surface of the rock to form a tight wrapping effect on the rock, and the phenyl-fluorine strong hydrophobic groups can extend outwards, so that the surface of the rock is converted from hydrophilicity to hydrophobicity, the water absorption of the rock is further greatly reduced, and the water blocking damage is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield exploitation, and in particular to a waterproof locking agent for oilfield fracturing and a production process thereof. Background Art

[0002] In the process of oil field exploitation, especially in the development of low-permeability oil and gas fields, measures to increase the production of oil and gas wells are crucial. As an effective means of increasing production, fracturing technology injects high-pressure liquid into the oil layer to form cracks, increase the permeability of the oil layer, and thus improve the recovery rate. However, during the fracturing process, the contact between oil and gas and foreign fluids often leads to an increase in reservoir water saturation and a significant decrease in the relative permeability of oil and gas, which in turn causes water lock damage. In order to effectively solve this problem, water-locking agents came into being and play an important role in oil field fracturing operations.

[0003] Waterproofing agents are chemical additives specifically designed to reduce or eliminate water lock damage. Its working principle is mainly based on the following aspects: Reduce surface and interfacial tension: Waterproofing agent molecules have low surface tension and interfacial tension, which enables them to effectively reduce the interfacial tension between the working fluid and the reservoir rock, reduce the spreading and penetration of the liquid on the rock surface, and thus reduce the water lock effect. Increase contact angle: Waterproofing agent molecules have a large contact angle, which means that when they come into contact with reservoir rocks, they can form a more hydrophobic surface. This hydrophobic property helps to prevent water from further penetrating into the rock, thereby reducing water lock damage. Good compatibility with working fluid: Waterproofing agents have good compatibility in working fluids, can be evenly dispersed and form a stable system with working fluids. This ensures that the waterproofing agent can fully play its role in the fracturing process without negatively affecting the performance of the working fluid.

[0004] However, existing waterproof locking agents usually have high surface tension, and the waterproof locking effect is not ideal, which is difficult to meet the needs. Based on this, the present invention provides a waterproof locking agent for oil field fracturing, which can solve the problems existing in the prior art. Summary of the invention

[0005] 1. Technical issues to be resolved In view of the deficiencies of the prior art, the present invention provides a waterproof locking agent for oil field fracturing and a production process thereof.

[0006] (II) Technical solution A production process of a waterproof lock agent for oilfield fracturing, the waterproof lock agent comprising the following raw materials in parts by weight: 0.6-1.5 parts of complex surfactant; 200-300 parts of purified water; The production process of the waterproof lock agent comprises the following steps: Step 1: weigh each raw material according to weight and set aside; Step 2: Add the composite surfactant into purified water and mix them by mechanical stirring to obtain a waterproof lock agent; The composite surfactant is prepared by using N-hydroxysulfonic acid succinimide and ethylene oxide as reactants to prepare an intermediate, and then using the intermediate to react with 3,5-bis(trifluoromethyl)phenyl isocyanate to prepare the composite surfactant.

[0007] As a further embodiment of the present invention, the specific preparation method of the composite surfactant is as follows: Step S1: Preparation of intermediate Tetrahydrofuran and N-hydroxysulfonic acid succinimide are added to a polymerization kettle, mechanically stirred evenly, nitrogen is introduced, air is exhausted, and then a catalyst is added to the polymerization kettle. After stirring for 20-40 minutes at a temperature of 50-55° C., ethylene oxide is added to the polymerization kettle. After the addition is completed, the temperature is further increased to 60-65° C., and the stirring is continued for 12-24 hours at the temperature. The nitrogen is removed, the heating is stopped, and the product is precipitated 2-3 times using dichloromethane as a solvent and petroleum ether as a precipitant to obtain an intermediate; Step S2: preparing a composite surfactant The intermediate is added to toluene, stirred and mixed to form a uniform reaction liquid, and then 3,5-bis(trifluoromethyl)phenyl isocyanate and a metal tin catalyst are added to the reaction liquid. After the addition is completed, the temperature is gradually increased to 70-80°C and maintained at this temperature for 8-12 hours to obtain a composite surfactant.

[0008] As a further solution of the present invention, in step S1, the specific preparation method of the catalyst is as follows: Under the protection of high-purity nitrogen, naphthalene and potassium block are added to tetrahydrofuran, and mechanical stirring is performed to make it uniform. Then, ultrasonic oscillation is performed at a temperature of 30-35° C. for 12-24 hours. Stirring is stopped, and the product is collected by filtration.

[0009] As a further embodiment of the present invention, the mass ratio of the naphthalene to the potassium block is 1:0.6-0.8.

[0010] As a further embodiment of the present invention, in step S1, the mass ratio of N-hydroxysulfonic acid succinimide to ethylene oxide is 1:10-15.

[0011] As a further embodiment of the present invention, in step S2, the metal tin catalyst is at least one of stannous octoate, dibutyltin dilaurate or dibutyltin diacetate.

[0012] As a further embodiment of the present invention, in step S2, the mass ratio of the intermediate to 3,5-bis(trifluoromethyl)phenylisocyanate is 1:0.2-0.3.

[0013] In the above technical scheme, N-hydroxysulfonic acid succinimide is first used as an active initiator, and ethylene oxide is subjected to ring-opening polymerization under the action of potassium naphthalene catalyst to obtain an N-hydroxysulfonic acid succinimide derivative containing a polyether structure, that is, an intermediate. Then, under the catalytic action of a metal tin catalyst, the active hydroxyl group at the polyether end of the intermediate structure can undergo an amine esterification reaction with the isocyanate group in the 3,5-bis(trifluoromethyl)phenylisocyanate structure, and finally a composite surfactant with a polyether as a connecting center is obtained.

[0014] A waterproof locking agent for oil field fracturing is prepared by adopting the above production process.

[0015] 3. Beneficial technical effects The composite surfactant prepared by the present invention contains both hydrophilic groups and hydrophobic groups in its structure, wherein the hydrophilic groups are sulfonic acid groups, succinimide and polyether, and the hydrophobic groups are phenyl fluoride, and thus it is an anionic and nonionic composite surfactant. Since the polyether has a linear structure, it can gradually extend into the cracks in the rocks and further enter into the deep capillaries, and then form hydrogen bonds with the rocks through the ether bonds in the polyether structure, and then adhere to the rock surface to form a tight wrapping effect on the rock, while the strong hydrophobic groups of phenyl fluoride can extend outward, so that the rock surface is converted from hydrophilic to hydrophobic, thereby greatly reducing the water absorption of the rock, thereby reducing water lock damage.

[0016] The waterproof lock agent prepared in the present application has low surface tension and interfacial tension, and can greatly increase the contact angle of the rock surface, and has high practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0018] Figure 1 This is the infrared analysis test diagram of the composite surfactant. DETAILED DESCRIPTION

[0019] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0020] Preparation Example 1 Preparation of composite surfactants Step 1: Preparation of catalyst Under the protection of high-purity nitrogen, 5 g of naphthalene and 3.5 g of potassium block were added to tetrahydrofuran, mechanically stirred evenly, and then ultrasonically vibrated for 16 h at a temperature of 30° C., stirring was stopped, and the product was collected by filtration to obtain a catalyst; Step 2: Preparation of intermediates Tetrahydrofuran and 0.3 g of N-hydroxysulfonic acid succinimide were added to a polymerization kettle, mechanically stirred evenly, nitrogen was introduced, and air was exhausted. Then 15 g of a catalyst was added to the polymerization kettle, and stirred for 30 min at 50° C., and 4 g of ethylene oxide was added to the polymerization kettle. After the addition was completed, the temperature was further increased to 60° C., and the mixture was kept warm and stirred for 16 h. Then, nitrogen was removed, heating was stopped, and the product was precipitated 3 times using dichloromethane as a solvent and petroleum ether as a precipitant to obtain an intermediate. Step 3: Preparation of composite surfactant 0.6 g of the intermediate was added to toluene, and the mixture was stirred to form a uniform reaction solution. Then, 0.15 g of 3,5-bis(trifluoromethyl)phenylisocyanate and 0.1 g of dibutyltin dilaurate were added to the reaction solution. After the addition was completed, the temperature was gradually increased to 75°C and maintained at this temperature for 9 hours to obtain a composite surfactant.

[0021] The composite surfactant was made into potassium bromide tablets and subjected to infrared analysis test. The results are shown in Figure 1 , of which 3000cm -1 ~3100cm -1 The characteristic absorption peak at 1758cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring skeleton. -1 and 1703cm -1 The characteristic absorption peaks at 1398 cm-1 are the C=O characteristic absorption peaks of the amine ester group and the imide group. -1 The characteristic absorption peak of S=O in the sulfonic acid group, 1341cm -1 The characteristic absorption peak at 1075cm is the CF characteristic absorption peak. -1 The characteristic absorption peak of CO of the ether bond appears at. Example 1

[0022] A waterproof locking agent for oilfield fracturing, comprising the following raw materials in parts by weight: 0.6 part of complex surfactant; 200 parts of purified water; The production process of the waterproof lock agent comprises the following steps: Step 1: weigh each raw material according to weight and set aside; Step 2: Add the composite surfactant into purified water, stir mechanically to mix well, and then the waterproof lock agent can be prepared. Example 2

[0023] A waterproof locking agent for oilfield fracturing, comprising the following raw materials in parts by weight: 1.2 parts of complex surfactant; 240 parts of purified water; The production process of the waterproof lock agent comprises the following steps: Step 1: weigh each raw material according to weight and set aside; Step 2: Add the composite surfactant into purified water, stir mechanically to mix well, and then the waterproof lock agent can be prepared. Example 3

[0024] A waterproof locking agent for oilfield fracturing, comprising the following raw materials in parts by weight: 1.5 parts of complex surfactant; 300 parts of purified water; The production process of the waterproof lock agent comprises the following steps: Step 1: weigh each raw material according to weight and set aside; Step 2: Add the composite surfactant into purified water, stir mechanically to mix well, and then the waterproof lock agent can be prepared.

[0025] Test Case ①, take 3 core pieces of the same specifications, place them in the waterproof lock agent of Example 1 to Example 3 respectively, then transfer them to a 120°C oven and let them stand for 24 hours, then take out the core pieces, dry them, and then perform a water contact angle test; ②. According to the standard SY / T 5370-2018 "Surface and interfacial tension determination method", the surface tension and interfacial tension of the waterproof lock agent in Example 1 to Example 3 are tested by the spinning drop method; The test results are recorded in Table 1: Table 1 - Test results

[0026] Note: "Commercially available" represents commercially available waterproof lock agent, which was purchased from Shanghai Futian Chemical Technology Co., Ltd.

[0027] From the analysis of the test results, it can be seen that the effect of the waterproof lock agent prepared by the present invention is significantly better than that of the commercially available waterproof lock agent, the lowest interfacial tension can reach 0.049mN / m, and the lowest surface tension can reach 21.3mN / m.

[0028] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A production process of a waterproof lock agent for oil field fracturing, characterized in that: The waterproof lock agent includes the following raw materials in parts by weight: 0.6-1.5 parts of complex surfactant; 200-300 parts of purified water; The production process of the waterproof lock agent comprises the following steps: Step 1: weigh each raw material according to weight and set aside; Step 2: Add the composite surfactant into purified water and mix them by mechanical stirring to obtain a waterproof lock agent; The composite surfactant is prepared by using N-hydroxysulfonic acid succinimide and ethylene oxide as reactants to prepare an intermediate, and then using the intermediate to react with 3,5-bis(trifluoromethyl)phenyl isocyanate to prepare the composite surfactant.

2. The production process of a waterproof locking agent for oil field fracturing according to claim 1, characterized in that: The specific preparation method of the composite surfactant is as follows: Step S1: Preparation of intermediate Tetrahydrofuran and N-hydroxysulfonic acid succinimide are added to a polymerization kettle, mechanically stirred evenly, nitrogen is introduced, air is exhausted, and then a catalyst is added to the polymerization kettle. After stirring for 20-40 minutes at a temperature of 50-55° C., ethylene oxide is added to the polymerization kettle. After the addition is completed, the temperature is further increased to 60-65° C., and the stirring is continued for 12-24 hours at the temperature. The nitrogen is removed, the heating is stopped, and the product is precipitated 2-3 times using dichloromethane as a solvent and petroleum ether as a precipitant to obtain an intermediate; Step S2: preparing a composite surfactant The intermediate is added to toluene, stirred and mixed to form a uniform reaction liquid, and then 3,5-bis(trifluoromethyl)phenyl isocyanate and a metal tin catalyst are added to the reaction liquid. After the addition is completed, the temperature is gradually increased to 70-80°C and maintained at this temperature for 8-12 hours to obtain a composite surfactant.

3. The production process of a waterproof locking agent for oil field fracturing according to claim 2, characterized in that: In step S1, the specific preparation method of the catalyst is as follows: Under the protection of high-purity nitrogen, naphthalene and potassium block are added to tetrahydrofuran, and mechanical stirring is performed to make it uniform. Then, ultrasonic oscillation is performed at a temperature of 30-35° C. for 12-24 hours. Stirring is stopped, and the product is collected by filtration.

4. The production process of a waterproof locking agent for oil field fracturing according to claim 3, characterized in that: The mass ratio of the naphthalene to the potassium block is 1:0.6-0.

8.

5. The production process of a waterproof locking agent for oil field fracturing according to claim 2, characterized in that: In step S1, the mass ratio of N-hydroxysulfonic acid succinimide to ethylene oxide is 1:10-15.

6. The production process of a waterproof locking agent for oil field fracturing according to claim 2, characterized in that: In step S2, the metal tin catalyst is at least one of stannous octoate, dibutyltin dilaurate or dibutyltin diacetate.

7. The production process of a waterproof locking agent for oil field fracturing according to claim 2, characterized in that: In step S2, the mass ratio of the intermediate to 3,5-bis(trifluoromethyl)phenyl isocyanate is 1:0.2-0.

3.

8. A waterproof locking agent for oil field fracturing, characterized in that: The method is prepared by the production process as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Acylated polyether polyol for petroleum recovery

    CA1136395A

  • Water dispersible polyisocyanate composition and preparation method thereof

    CN109517139A

  • Waterproof locking agent for fracturing and preparation method thereof

    CN114958330A

  • Super-hydrophobic nano-material water lock removing agent and preparation method thereof

    CN115850553A

  • Regulator for water film in pores of hydrophilic reservoir as well as preparation method and application of regulator

    CN116987269A